G Protein-Coupled Estrogen Receptor in Immune Cells and Its Role in Immune-Related Diseases - Notas, George; Kampa, Marilena; Castanas, Elias (Frontiers in Endocrinology, 2020)
G protein-coupled estrogen receptor 1 (GPER1), is a functional estrogen receptor involved in estrogen related actions on several systems including processes of the nervous, reproductive, metabolic, cardiovascular, and immune system. Regarding the latter, GPER is expressed in peripheral B and T lymphocytes as well as in monocytes, eosinophils, and neutrophils. Several studies have implicated GPER in immune-mediated diseases like multiple sclerosis, Parkinson’s disease, and atherosclerosis-related inflammation, while a recent report suggests that its deletion could be responsible for a form of familial immunodeficiency. It has also been suggested that it is a key regulator of immune-mediated events in breast, pancreatic, prostate, and hepatocellular cancer as well as in melanoma. GPER has been also reported to interact with classic ER-alpha or its splice variants in order to modify immune functions. This review aims to present current knowledge relating GPER to immune functions, the cellular and signaling pathways involved, as well as the potential clinical implications of GPER modulation in immune-related diseases.